Can academia be decolonized beyond the metaphor? - Pérez, Moira Patricia (2022)
The paper evaluates the reach and viability of the call to “decolonize academia” and assesses what can be done in academic institutions by way of decolonizing practices. By distinguishing colonialism from coloniality, it stresses the material and structural dimensions of the latter as an on-going reality, and thus argues for the impossibility of “decolonizing” the academy as we know it. From this stance, it identifies an array of expressions of coloniality in the academy and presents a critique of metaphorical and/or allegedly performative approaches to decolonization. In doing this, the paper seeks to offer philosophical instruments for a thorough, self-critical reflection and intervention on academic institutions and teaching and research practices, in the understanding that these must be but a part of broader processes of social transformation.